2003
DOI: 10.1016/s0140-1971(02)00118-5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent resilience: a concept analysis

Abstract: There is need for greater clarity around the concept of resilience as it relates to the period of adolescence. Literature on resilience published between 1990 and 2000 and relevant to adolescents aged between 12‐ and 18‐years of age was reviewed with the aim of examining the various uses of the term, and commenting on how specific ways of conceptualizing of resilience may help develop new research agendas in the field. By bringing together ideas on resilience from a variety of research and clinical perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
435
0
37

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 687 publications
(504 citation statements)
references
References 35 publications
14
435
0
37
Order By: Relevance
“…The importance of supportive families, schools and peers has been well described [1,29,30], but rarely in relation to positive health. The results will first discuss students’ health in relation to participation in the classroom and then relate this to support from teachers, pupils and parents and then in relation to personal affluence.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of supportive families, schools and peers has been well described [1,29,30], but rarely in relation to positive health. The results will first discuss students’ health in relation to participation in the classroom and then relate this to support from teachers, pupils and parents and then in relation to personal affluence.…”
Section: Discussionmentioning
confidence: 99%
“…Young people who function well under high stress have often displayed higher levels of emotional distress compared to low stress peers (Olsson, Bond, Burns, Vella-Broderick & Sawyer, 2003).…”
Section: Psychological Resilience and Prospective Academic Achievementmentioning
confidence: 99%
“…Investigators have also suggested that resilience can be conceptualized as a process. 32 It changes within and across time, and adaptation results from the interaction of risks and protective factors. Specifically, the protective factors at multilevels can enhance the individual's capacity to respond or adapt to adverse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the protective factors at multilevels can enhance the individual's capacity to respond or adapt to adverse conditions. 32,61 From the National Youth Survey of Adolescents, multilevel factors predicted or mitigated problem behaviors. 31 Youth who spent longer time with deviant friends and less time with family had higher levels of problem behaviors over time while those spending more time with family perceived greater family support and exhibited fewer problem behaviors.…”
Section: Discussionmentioning
confidence: 99%